(untitled) (Green Life Medical College Journal, 2026)
Choanal atresia is a rare congenital obstruction of the posterior nasal aperture. Unilateral choanal atresia may remain undiagnosed until adulthood and typically presents as chronic unilateral nasal obstruction. A 21-year-old female presented with right-sided nasal obstruction and intermittent snoring since childhood. She had undergone adenotonsillectomy at 11 years of age without improvement. Examination revealed septal deviation to the left, right inferior turbinate hypertrophy, and absent right nasal airway patency. Nasal endoscopy identified a right posterior choanal atretic plate, and computed tomography of the paranasal sinuses confirmed complete right-sided mixed choanal atresia. The patient was treated with endoscopic transnasal posterior septectomy and removal of the atretic plate. Recovery was uneventful. Follow-up endoscopy at 1 and 4 months demonstrated a widely patent neochoana with complete symptom resolution. Adult unilateral choanal atresia is uncommon and often misdiagnosed. Clinicians should consider this diagnosis in patients with lifelong unilateral nasal obstruction, and endoscopic transnasal posterior septectomy offers a safe and effective treatment option. Journal of Green Life Med. Col. 2026; 11(1): 30- 32